Motor Competence in Adolescents: Exploring Association with Physical Fitness - Thórdís Gísladóttir; Monika Haga; Hermundur Sigmundsson (MDPI AG, 2019)
The purpose of this study was twofold: First, to examine the correlation between adolescents’ performance on the Movement Assessment Battery for Children -2 (MABC-2) and the Test of Motor Competence (TMC), and second, to interpret the correlation between performance on physical fitness measures and motor competence. This study had a cross-sectional design, in which 101 adolescents age 15−16 years were recruited. The participants were assessed with the MABC-2 (eight tasks), the TMC (four tasks) and physical fitness measures (four tasks). Ninety-four participants completed all the test items (51% male). The correlation between the standard score of the MABC-2 and TMC total score was found to be moderate (r = −0.418). A weak correlation was found between MABC-2 and total score of physical fitness (r = 0.278), while the correlation between TMC and physical fitness was a little stronger (r = 0.361). However, when removing one measure from the TMC (the walking/running in slopes), the correlation was weak and not significant (r = 0.109). The results suggest that different test batteries can cause discrepancy in the results regarding correlation between motor competence and physical fitness in adolescents.